Histological diagnosis of chronic inflammatory bowel disease in childhood. Issue 1 (January 1985) - Chong, S K; Blackshaw, A J; Boyle, S; Williams, C B; Walker-Smith, J A
Abstract : One hundred and four children were initially assessed by clinical, radiological, and endoscopic criteria as chronic inflammatory bowel disease. All were assessed independently using precise histological diagnostic criteria. Fifty eight patients were diagnosed as Crohn's disease, 25 as ulcerative colitis, 15 remained provisionally categorised as indeterminate colitis and six proved to be normal. Diagnostic granulomas were found in 36% of endoscopic biopsies from the 58 children with Crohn's disease. This appears to be an underestimate as only four of 14 children with granulomatous Crohn's disease operated on had granulomas on endoscopic biopsy. This study shows that there is a spectrum of histological appearances in endoscopic biopsies in chronic inflammatory bowel disease in childhood ranging from definite Crohn's disease to definite ulcerative colitis with indeterminate features in between. Accurate histological diagnosis of chronic inflammatory bowel disease is dependent upon either multiple endoscopic biopsies or assessment of a surgically resected specimen.